2014
DOI: 10.1177/1046878114554191
|View full text |Cite
|
Sign up to set email alerts
|

The Gaming Involvement and Informal Learning Framework

Abstract: This article presents a model of how gaming involvement and informal learning come together in practice. Based on a series of interviews, case studies and a wider survey, the Gaming Involvement and Informal Learning (GIIL) framework indicates how involvement with a variety of gaming practices can lead to a range of different learning experiences. The framework is able to account for both how and what people learn from gaming while also highlighting the influence of player identity. Further, the iterative relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
2
18
0
2
Order By: Relevance
“…Rotman et al [2012] found that volunteers' initial interests in environmental projects stemmed from factors such as personal curiosity and previous engagement in citizen science; while ongoing participation was affected by factors such as recognition, attribution, feedback, community involvement and advocacy. Iacovides et al [2014] found similar results in their study with Foldit and Eyewire volunteers: motives for joining a project included having an interest in science and being pro-citizen science; while sustained engagement was influenced by factors such as recognition, gaming elements, and team-play.…”
Section: Motivationssupporting
confidence: 63%
“…Rotman et al [2012] found that volunteers' initial interests in environmental projects stemmed from factors such as personal curiosity and previous engagement in citizen science; while ongoing participation was affected by factors such as recognition, attribution, feedback, community involvement and advocacy. Iacovides et al [2014] found similar results in their study with Foldit and Eyewire volunteers: motives for joining a project included having an interest in science and being pro-citizen science; while sustained engagement was influenced by factors such as recognition, gaming elements, and team-play.…”
Section: Motivationssupporting
confidence: 63%
“…While the majority of participants engaged with the playtesting and noted positives as well as negatives regarding the different games, one participant in particular struggled with the process: This exchange highlights the fact that engagement normally starts off as a choice [4], and is influenced by multiple micro and macro level factors [12]. Regardless of subject matter, for those that expect to engage in more lightweight and familiar forms of gameplay and who aren't willing to revise their initial expectations, serious experiences will not lead to engagement, let alone further reflection.…”
Section: Limitationsmentioning
confidence: 99%
“…While engagement may have been influenced by how players identified as gamers [23], this was not something that seemed to come out of the focus groups. However, future research could be carried out to explicitly focus on the influence of prior gaming experience on engagement and learning within a SCG.…”
Section: Limitations and Future Workmentioning
confidence: 99%